A knowledge, attitude, and practice study to identify factors associated with refusal of post-partum sterilization - Tapasvi, Isha; Rajora, Parveen; Grover, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Aim of the study was to identify awareness among parturient women about the advantages of postpartum sterilization and common factors associated with its refusal. This study was conducted in Department of Obstetrics and Gynecology, GGS Medical College and Hospital, Faridkot. A cross-sectional study in women who delivered between August 2020 and March 2021 and gave consent. Methods: A total of 200 patients who refused postpartum sterilization were included as per the inclusion and exclusion criteria. Data collection included a questionnaire to assess their knowledge for this procedure and the reasons for refusal, age, socio-economic status, education status, occupation of head of family, family income, awareness of advantages and disadvantages and also prevalence of various misconceptions. Results: The 38 cases (19%) of refusals were of 20-24 years age group with maximum incidence 38.5% in 25-29 years. The chief reason for refusal was the desired chance for male child in next pregnancy resulting in maximum refusals 143 out of 200 (72%). Socioeconomic factors, educational background and work profile of the patients and family members also had influence in the decision of refusal. There were certain misconceptions in relation to refusals with almost 90% gave no preference to vasectomy, possibility of weight gain in 51%, disturbance in carrying daily work routine in 84%. Conclusions: This study suggests need of better counselling by the healthcare workers to implement small family norm which in turn can aid to reduce maternal mortalities.